The Effect of Binders on the Quality of Fermented Poultry Manure Pellets as Unconventional Feed - A. N. Prastiwi; A. R. D. Wardani; C. T. Noviandi; A. Astuti; D. H. V. Paradhipta (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
Poultry manure has the potential to be used as a feed ingredient because it has a high enough protein and amino acid with less growth of patoghenic microorganism. The improvement of poultry manure as pellet can help to increase the palatability and feed storaging. This study aimed to determine the influence of different binders on the chemical and physical attributes of pellets derived from fermented poultry manure. Three binders, namely tapioca flour (T1), wheat flour (T2), and cassava flour (T3), were utilized in the fermentation process, with the fermented poultry manure. A 10% binder was added into the mixture, which was subsequently processed using a pelletizer. Each treatment was replicated three times, with each replication requiring 1500 g of the pellet mixture. Laboratory analyses were conducted to evaluate chemical quality through proximate analysis and gross energy assessment, while physical quality analyses included physical characteristics, measurements of diameter, length, and density, stacking density, stack compaction density, pellet durability index (PDI), modulus of uniformity, modulus of fineness, buoyancy, and water resistance. The results indicated that variations in binders did not yield numerically differences in dry matter content, organic matter, crude fat, crude fiber, and gross energy. Notably, pellets containing a wheat flour binder exhibited the highest crude protein content numerically. Furthermore, influenced the buoyancy test, with wheat flour binder showing the best buoyancy. This study recommends the adoption of wheat flour as a binder in the production of pellets based on fermented poultry manure.